(untitled) (Journal of International Studies, 2015)
The ASEAN Community is expected to be formalized on 31 December 2015. The task of seeing the materialization of the much awaited project has fallen on Malaysia which is currently holding the Chair. The Malaysian team led by the Prime Minister, Dato’ Sri Mohd Najib Tun Abdul Razak is not only making the necessary preparations to host the summit, but is also trying to complete the multitude of uncompleted tasks connected with the integration process. This paper outlines the major milestones that ASEAN has achieved since the organization began to toy with the idea of community formation in 2000 to the present time (October 2015). The paper will then examine the major challenges and shortcomings faced by ASEAN as well as some of the measures crafted by the organization to overcome them.